Physical and Mental Health Experiences among African American College Students. Issue 2 (17th February 2019) - Barnett, Tracey Marie; McFarland, Ashston; Miller, John W.; Lowe, Victoria; Hatcher, Schnavia Smith
ABSTRACT: Transitioning from home to college life can lead to changes in dietary and physical activity behaviors. Approximately 12% to 50% of college students meet criteria for one or more mental disorders. When compared to others, African Americans typically have poorer health outcomes and experience greater rates of cardiovascular-related diseases and depression. The purpose of this qualitative interpretive meta-synthesis (QIMS) was to understand physical and mental health experiences among African American college students to inform policy, practice, and research. Findings from the QIMS revealed two overarching themes: (1) perceptions of physical health and (2) perceptions of mental health. Each theme included three dimensions. The dimensions of perceptions of physical health include (1) exercising for health benefits, (2) exercising for aesthetics, and (3) nutrition versus healthy eating. The dimensions of perceptions of mental health include (1) stress, (2) confidence, and (3) spirituality. These themes enhance understanding of what African American college students perceive and experience when attempting to engage in overall physical and mental health.